Search for a diffuse flux of extragalactic neutrinos with the IceCube neutrino observatory - Schukraft, Anne (Publikationsserver der RWTH Aachen University, 2013)
Since the discovery of cosmic rays it has been one of the major research goals to identify the sources and acceleration mechanisms behind these high-energy particles observed from space, with energies up to several EeV. The study of high-energy charged particles and photons has advantages and disadvantages: the detection techniques for charged cosmic rays are very advanced though high-energy charged nuclei are not able to reveal their sources due to magnetic deflection. In the last years, there have been discoveries of many gamma-ray sources, where photon fluxes up to energies of 100 TeV have been observed. However, the universe is opaque to photons with energies larger than 100 TeV since gamma rays interact with the cosmic microwave background. Neutrinos suffer from neither of these limitations. They are ideal messenger particles in order to investigate the sources of cosmic rays since they propagate unaffected, but their detection is difficult and no extraterrestrial neutrino sources at high energies have yet been found. The IceCube experiment, located at the geographic South Pole, was built in order to detect high-energy neutrinos from the universe. It was completed in December 2010 and is the largest neutrino observatory on Earth. It detects neutrinos via their interaction with the Antarctic ice inside and around the detection volume. In these interactions, high-energy leptons are produced, which follow the direction of the initial neutrino and produce a cone of Cherenkov light along their path. This light is detected by optical sensors deployed in the instrumented volume. The search for a diffuse neutrino flux is a very promising approach to look for an extragalactic flux of astrophysical neutrinos. Its sensitivity is mainly based on neutrino energies since astrophysical neutrinos are expected to be more energetic than atmospheric neutrinos. It searches for an astrophysical flux from the sum of all sources in the universe. These sources can be individually weak and not yet resolvable as point-like objects. ...